CURRICULUM 2013 IN RELATION TO EDUCATION FOR SUSTAINABLE DEVELOPMENT IN INDONESIA: - Rusli Rusli (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2018)
This paper explores curriculum 2013 in conjunction with education for sustainable development in Indonesia. Reorientation in education could be considered as an effort for producing skilled human resources in order to deal with transition period toward sustainable development. Curriculum 2013 should be focused on issues referring to education for sustainable development. Learning approach in curriculum 2013 should be combined with educational learning and teaching about knowledge, issues, skills, perspective, and values that lead to student much more motivate to achieve the goals of sustainable development through respect- ful to the others either current generation or the next generation, respectful to the earth that provides natural resources for the human beings.